Ghana’s National Health Insurance enrollment: Does the intersection of educational and residential status matter? - Roger Antabe; Florence W. Anfaara; Yujiro Sano; Daniel Amoak (PLoS ONE, 2025)
Background Since its inception in 2003, Ghana’s Health Insurance Scheme (NHIS) has received considerable scholarly attention on the determinants of enrollment. While most of these studies highlight the role of some socioeconomic and geographical factors, no study has explored the intersection of educational attainment and residence on NHIS enrollment. We aim to contribute to the literature and health policy in Ghana by examining the intersection of educational attainment and rural-urban residence on NHIS enrollment among women and men. Methods We used nationally representative data from the 2022 Ghana Demographic and Health Survey (GDHS). Using STATA 17, we applied multivariable logistic regression to our analytical sample comprising women (n = 14997) and men (n = 7040). Results Overall, we found that more women (90%) than men (73%) enrolled on the NHIS. Adjusting for a range of control variables, we found that women and men with secondary (OR: 1.61, 95% CI: 1.28–2.02; OR: 1.45, 95% CI: 1.16–1.82) and higher education (OR: 1.81, 95% CI: 1.24–2.64; OR: 2.85, 95% CI: 2.03–3.99) were more likely to have enrolled into the NHIS compared to those with no formal education. This difference was particularly heightened among women and men with no education. Rural women (96%) and men (90%) with higher education had higher enrollment rates compared to their urban counterparts. Conclusion We recommend revising the NHIS equity and pro-poor policy to include vulnerability at the intersection of low educational attainment and rural residence.